Immunohistochemical analysis of P53 protein in odontogenic cysts - Essam Taher M.A. Gaballah; Mohamed A. Tawfik (Elsevier, 2010)
The p53 is a well-known tumor suppressor gene, the mutations of which are closely related to the decreased differentiation of cells. Findings of studies on immunohistochemical P53 expression in odontogenic cysts are controversial. The present study was carried-out to investigate the immunohistochemical expression of P53 protein in odontogenic cysts. Thirty paraffin blocks of diagnosed odontogenic cysts were processed to determine the immunohistochemical expression of P53 protein. Nine of the 11 odontogenic keratocysts (81.8%) expressed P53, one of three dentigerous cyst cases expressed P53, while none of the 16 radicular cysts expressed P53 protein. The findings of the present work supported the reclassification of OKC as keratocystic odontogenic tumor. Keywords: P53, Odontogenic cysts, Odontogenic keratocysts, Radicular cysts, Dentigerous cysts